PENGARUH PENERAPAN TEKNIK QUICK ON THE DRAW TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 02 RAO KABUPATEN PASAMAN TAHUN PELAJARAN 2012/2013 - Nurhabibah, Nurhabibah; Aima, Zulfitri; Cesaria, Anna (STKIP PGRI Sumbar, 2013)
This research are less of the studentâs activity and the low of the studentâs comprehention mathematics concept in the learning process. The purpose of this research is to know how the studentâs activityÂ during learning process that apply technique Quick on The Draw and to determine that students comprehension mathematicalâs concept by implementation of technique Quick on The DrawÂ better than students comprehension mathematicalâs concept by implementation conventional learning in the class VIII SMPN 2 Rao Pasaman. The research type is experimental research, and the design was subject with a random. The population this research are students of class VIII SMPN 2 Rao Pasaman Academic Year 2012/2013. Samples were taken at random. The instrument in this research are observation sheet and final test students comprehension mathematicalâs concept. The test form of essay test with reliability test 0,83. Based on result of analysis observation sheet gain that the student more active during learning process that apply technique Quick on The Draw. The data analysis sectionÂ is U Mann-Whitney test by using Minitab. Hypotesis of research accepted because p-value Â less than 0,05. Thus, it can be concluded that students comprehension mathematicalâs concept by implementation of technique Quick on The Draw better than students comprehension mathematicalâs concept by implementation conventional learning in the class VIII SMPN 2 Rao Pasaman Academic Year 2012/2013..